The Pathophysiological Mechanisms and Pattern of Dyslipidemia Associated with Iodine Deficiency and Subclinical Hypothyroidism in Pregnant Normotensive and Preeclamptic Central African Women - Charles Bitamazire Businge; Benjamin Longo-Mbenza (Pathophysiology, 2025)
Background: Pregnancy simulates a metabolic syndrome-like state and predisposes to iodine deficiency and hypothyroidism through increased iodine renal loss and transplacental transfer to the fetus. Iodine deficiency is thought to predispose to dyslipidemia through elevation of serum TSH. Obesity, dyslipidemia, and hypothyroidism are established risk factors of preeclampsia. Hence, pregnant women with iodine deficiency are likely to be at increased risk of dyslipidemia and preeclampsia. We investigated the pattern of dyslipidemia among preeclamptic and normotensive pregnant women with and without iodine deficiency. Methods: The pathophysiological mechanisms linking iodine deficiency and dyslipidemia were delineated using bivariate correlations, logistic regression, and exploratory factor analysis of anthropometric, lipid profile, urine iodine concentration (UIC), and thyroid function data from 240 women with preeclampsia and 120 normotensive pregnant controls at term who attended Lomo Medical Centre, Democratic Republic of Congo (DRC). Results: Preeclamptic women with iodine deficiency had significantly lower HDL-C but higher triglyceride levels than those with sufficient iodine intake. Both normotensive and preeclamptic participants with elevated TSH had high serum oxidized LDL-C but low NO, p < 0.001. Conclusions: SCH, secondary to iodine deficiency, is associated with elevated serum oxidized LDL and decreased Nitric Oxide (NO) among both normotensive and preeclamptic women, while insufficient iodine nutrition among preeclamptic women predisposes to reduced HDL-C and increased serum Triglycerides, which are risk factors of atherosclerosis and cardiovascular disease.